Learners' Autonomy in The Midst of Covid-19 Pandemic - Tri - Mulyati (Universitas PGRI Yogyakarta, 2022)
This study aims to analyze the student's perception of learning autonomy in the midst of the Covid-19 Pandemic. The outbreak of this pandemic has switched the learning activities from face-to-face mode to online one. The students in all levels of education institutions, from kindergarten to university, have learned from home since March 2020. This condition yields some challenges among students. Thus, the students' voice dealing with learning autonomy is one of the essential sources to evaluate and redesign Self-Directed Learning during the pandemic. The questionnaire included 30 items was developed. It covered three aspects of learning autonomy, namely, learning planning, monitoring and organizing, and evaluating learning. Seventy-eight students of the English Department participated in this cross-sectional survey. The results reveal that most students have inadequate learning autonomy during online learning mode. The dependency on the lecturers' role is still found as they are not used to online learning before.